Women and the Language of Statistics in Late-Nineteenth-Century France: Reading the Graphs of Madame Pégard. Issue 3 (1st December 2019) - Périvier, Hélène; Rogers, Rebecca
Abstract : This article considers how women adopted a "scientific" statistical language at the end of the nineteenth century to draw attention to their role in the moral and social economy. It explores in particular the messages contained in La Statistique générale de la femme française, a series of eighteen murals that the moderate feminist Marie Pégard sent for exhibition at the Woman's Building at the Chicago World's Fair in 1893. The article begins by considering the place statistics held in France in the final decades of the century within the context of universal exhibitions. It then examines Pégard's choice of quantified categories of social analysis to convey a sustained argument about the comparative weight of women in a modernizing French economy. The article seeks to understand how contemporaries read and interpreted the graphs, and how this mode of rendering visible the issue of women's work played into the politics of an emerging feminist movement.